Study of Sorption Activity of Carbon Nanomaterials for Capture of Chlorine-Containing Gases - Yulia Ioni; Victoria Ibragimova (Clean Technologies, 2025)
Chlorine gas and hydrogen chloride are highly reactive chemicals that pose a significant hazard to living organisms upon direct contact. Also, chlorine-containing gases are often by-products of industrial chemical synthesis and can be released into the air as a result of accidents. This can lead to great pollution of the environment. To remove toxic gases, various filter systems can be used. Filters based on carbon nanomaterials can be suitable for capturing gaseous chlorine-containing substances, preventing their spread into the air. In this work, the sorption activity of various carbon-based nanomaterials (graphene oxide, modified graphene oxide, reduced graphene oxide, multi-walled carbon nanotubes, carbon black) in relation to gaseous chlorine and hydrogen chloride was investigated for the first time. It has been shown that employed carbon nanomaterials have an excellent ability to remove chlorine and hydrogen chloride from the air, exceeding the performance of activated carbon. Modified graphene oxide with an increased surface area showed the highest sorption capacity of 73.1 mL HCl and 200.0 mL Cl2 per gram of the sorbent, that is almost two and five times, respectively, higher than that of activated carbon. The results show that carbon nanomaterials could potentially be used for industrial filters and membrane fabrication.